Examining factorial validity and internal consistency of Professional Quality of Life (ProQoL-9) among care aides working in Long-term Care (LTC) - Seyedehtanaz Saeidzadeh; Anni Wang; Yinfei Duan; Isaiah Hipel; Peter G. Norton; Carole A. Estabrooks (BMC Health Services Research)
Abstract Background The ProQoL (30 items) is a widely used instrument of work-related quality of life for health care workers. Recently, a shorter 9-item version of the ProQoL was developed and validated among palliative care workers. The ProQoL-9 consists of three subscales: compassion satisfaction (CS), burnout (BO), and compassion fatigue (CF). Care aides (personal support workers, nursing assistants) are an understudied population in terms of their professional quality of life. It is critical to use validated instruments to measure their experiences. The purpose of this study was to examine the internal consistency and factorial structure of the ProQoL-9 among care aides working in LTC. Methods We used surveys collected by the Translating Research in Elder Care (TREC), a pan-Canadian program that collects longitudinal surveys from the healthcare workforce in the LTC. We used TREC surveys containing information on demographics, characteristics of LTC homes (e.g., ownership model), and the ProQoL-9. Our sample included all care aides who completed TREC surveys in the province of Alberta, Canada, from 2020–2021. We examined internal consistency via alpha and omega coefficients. To examine the factorial structure, we conducted confirmatory factor analysis (CFA) testing one factor, two factors (CF and BO together & CS), and three factor models (CF, BO, and CS). Results N = 760 care aides completed the surveys in Alberta. The majority were female (90.79%) and worked in general LTC units (55.29%). The Cronbach’s alpha results showed an overall α = 0.56 for the whole scale and adequate reliability of the subscales (α = 0.73 for CS, α = 0.68 for CF, and α = 0.75 for BO). The omega reliability results for all the subscales were ≥ 0.70, reflecting good internal consistency (BO = 0.77, CS = 0.73, and CF = 0.70). The three-factor model had the best goodness of fit values, reflecting an adequate goodness of fit (X2 = 165.82, DF = 24, X2/DF = 6.9, P < .0001, RMSEA = 0.08, CFI = 0.92, TLI = 0.89). Conclusions The ProQoL-9 is a valid and reliable instrument among care aides in LTC. The factorial structure shows that this shorter version of the ProQoL is rigorously designed and can be utilized by health service researchers in LTC.